Method for efficiently removing carbon deposit on catalyst

Through the electro-strengthening CO2 carbon removal method, the catalyst surface area carbon is driven by current to react with CO2, which solves the problems of high energy consumption and inaccurate temperature control in the prior art, and realizes an efficient and real-time monitoring carbon removal process, which improves the catalyst activity recovery effect.

CN119500288APending Publication Date: 2025-02-25INST OF ELECTRICAL ENG CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411704511.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When removing carbon deposits on catalysts, the prior art has high energy consumption, inaccurate temperature control, and it is difficult to monitor the changes in the surface area of ​​the catalyst in real time, resulting in inaccurate carbon removal process.

Method used

By using the electro-strengthening CO2 carbon removal method, by energizing the catalyst, an electric current in the carbon deposit passes through and reacts with CO2 and is removed. The change in the carbon deposit amount is monitored in real time by using the catalyst's resistance changes.

Benefits of technology

It reduces carbon removal energy consumption, improves energy utilization efficiency, shortens carbon removal time, realizes real-time monitoring and feedback control, and improves the catalyst activity recovery effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500288A_ABST
    Figure CN119500288A_ABST
Patent Text Reader

Abstract

The invention discloses a method for efficiently removing carbon deposition on a catalyst. The method provided by the invention comprises the following steps: electrifying the catalyst, wherein current passes through carbon deposition on the catalyst and reacts with CO2 to be removed. The device has the advantages of being high in energy efficiency and practicability, capable of achieving simultaneous chemical production and catalyst carbon removal and the like, particularly, the carbon deposition change on the surface of the catalyst can be observed in real time by monitoring the resistance change of the catalyst, and good conditions are provided for feedback control of the carbon removal process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalytic technology, and in particular to a method for efficiently removing carbon deposits on a catalyst. Background Art

[0002] In industrial production such as petrochemicals and coal chemical industry, carbon deposits are often easily formed during the use of catalysts, especially under high temperature, high pressure and complex reaction conditions. The formation of carbon deposits will not only reduce the activity of the catalyst and lead to a decrease in reaction efficiency, but may also block the pores of the catalyst, affecting the diffusion of reactants and products, and even lead to catalyst deactivation and equipment damage in severe cases. Therefore, how to efficiently remove carbon deposits on catalysts has always been a hot issue of concern to industry and academia.

[0003] At present, there are mainly physical and chemical methods for removing carbon deposits on catalysts. Although physical methods such as mechanical friction (CN118387834A) and ultrasonic treatment (CN116983909A) are relatively simple to operate, it is often difficult to completely remove carbon deposits and may cause mechanical damage to the catalyst. In industry, chemical methods are more commonly used to remove carbon deposits. The most typical method is to use high temperature to react carbon deposits with oxygen in the air to generate gases such as carbon dioxide, thereby achieving the purpose of removing carbon deposits. However, such methods usually generate a large amount of heat on the surface of the catalyst, thereby generating hot spots locally on the catalyst, causing changes in the structure of the active components of the catalyst, and even deactivating it. For this reason, attempts have been made to explore the removal of carbon deposits at lower temperatures and lower oxygen partial pressure atmospheres (such as CN104084218A, CN104107704A, etc.), but it is often time-consuming and energy-intensive, and the effect of catalyst activity recovery is not ideal. In order to improve the effect of removing carbon deposits, some people also use mixed airflows such as ozone-oxygen (CN104507566A) and carbon dioxide-oxygen (CN107971046A) to remove surface carbon. Although this method can reduce the operating temperature, thereby reducing the probability of sintering of the active components of the catalyst, the process conditions are relatively complex, the temperature control accuracy is not high, but the energy consumption is very high, and it is impossible to monitor the changes in the carbon deposit on the catalyst surface in real time. The carbon removal situation can only be indirectly understood by sampling and analyzing the composition of the atmosphere flowing out of the reactor. There is a significant time lag, and it is difficult to accurately control the carbon removal process. Summary of the invention

[0004] In order to solve the above problems existing in the prior art, the present invention proposes a method for efficiently removing carbon deposits on a catalyst. 2 Carbon removal method. The method of the invention has the advantages of high energy efficiency, strong practicability, and the ability to monitor the change of carbon deposits in real time.

[0005] The present invention provides a method for efficiently removing carbon deposits on a catalyst, specifically, electrifying the catalyst so that the current passes through the carbon deposits on its surface and reacts with CO 2 The reaction was removed.

[0006] Optimally, the temperature of the catalyst can be adjusted by varying the current.

[0007] Preferably, the catalyst is a conductive structured catalyst.

[0008] Optimally, the active component of the catalyst contains Ni.

[0009] Optimally, carbon deposits are formed by methane cracking reactions.

[0010] Optimized, real-time monitoring of carbon deposit changes through changes in catalyst resistance.

[0011] The beneficial effects of the present invention include: (1) The present invention uses a method of passing current through carbon deposits to separate C and CO 2 The chemical reaction between them can reduce the energy consumption of carbon removal.

[0012] (2) The present invention uses the method of electrifying the catalyst to provide energy for the carbon removal process, avoiding the convection and radiation heat transfer processes in the traditional external heating method and improving the energy utilization efficiency.

[0013] (3) The present invention utilizes the Joule heat generated by the catalyst itself when it is electrified to adjust the catalyst temperature, which has the advantages of fast temperature rise and fall speed, reduces the time required for the carbon removal process, and improves production efficiency.

[0014] (4) The present invention can observe the changes in carbon deposition on the catalyst surface in real time by monitoring the changes in the resistance of the catalyst, thus providing good conditions for feedback control of the carbon removal process.

[0015] (5) The method of the present invention uses carbon dioxide with relatively stable chemical properties as a carbon removal agent, which can be introduced into the reactor together with the feed gas, and the Joule heat of the electric current is used to simultaneously drive the chemical production and the carbon removal of the catalyst, which helps to improve the activity of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The foamed nickel-chromium-aluminum structured catalyst was used for CH 4 Carbon deposits and CO 2 Carbon removal process; Figure 2 The foamed nickel-chromium-aluminum structured catalyst was used for CH 4 Carbon deposits and CO 2 Carbon removal process; Figure 3 The CO of the present invention and the conventional external heating method2 Comparison of CO mass spectrometry signals during carbon removal process. DETAILED DESCRIPTION

[0017] The present invention is further described below in conjunction with the following embodiments and comparative examples, but the present invention is not limited by these embodiments and comparative examples.

[0018] Example 1 This example is to use nickel-chromium-aluminum foam structured catalyst to react methane carbon with CO 2 The carbon removal process illustrates the feasibility of the application of the method of the present invention.

[0019] The cleaned and dried nickel-chromium-aluminum foam (size 70 mm 4 mm 1mm) was put into a hydrothermal reactor filled with 0.25mol / l urea aqueous solution, and the hydrothermal reaction was carried out at 110℃ for 8 hours. The precursor was taken out and dried; then, 2 The catalyst (i.e., foamed nickel-chromium-aluminum structured catalyst) was obtained by calcining in an atmosphere of N2O / Ar (volume ratio of 1:9) and at 750°C for 2 hours.

[0020] Copper terminals are installed at both ends of the catalyst, which are placed axially in the middle of the quartz tube reactor. Copper wires are connected to both ends of the catalyst to lead out of the reactor from both ends of the quartz tube and connected to the positive and negative poles of a high-precision constant current DC power supply. Current sensors and voltage sensors are used to obtain real-time resistance changes of the catalyst. An online gas mass spectrometer is used to monitor real-time changes in the gas composition flowing out of the reactor, and a mass flow meter is used to control the flow of each gas.

[0021] The CH 4 Carbon deposits and CO 2 The method of carbon removal is as follows: i. Ar (30 ml / min) is introduced into the quartz reactor, and after the air is exhausted, the catalyst is energized at a preset current intensity (3.3 A or 4.8 A) to increase the temperature; ii. After the catalyst temperature stabilizes, introduce CH 4 (6 ml / min) and reduce Ar to 24 ml / min. After 30 min, turn off CH 4 and increase Ar to 30 ml / min; iii After passing Ar for 10 minutes, pass CO 2 (6 ml / min) and reduce Ar to 24 ml / min, and turn off CO after 30 minutes. 2 and increase Ar to 30 ml / min.

[0022] The gas mass spectrometer signals and the resistance, electric power and temperature signals of the catalyst in the above process are all recorded in real time.

[0023] At 3.3A current (such as Figure 1 As shown in the figure, the gas mass spectrometry signal shows that the methane cracking reaction is not activated. With the switching of the atmosphere, the resistance signal of the catalyst undergoes a sudden change synchronously, which is related to the change of the catalyst resistance by the adsorption of different gases. The resistance value of the catalyst exposed to the Ar atmosphere three times remains unchanged, indicating that the above changes are reversible.

[0024] At 4.8A current (such as Figure 2 As shown), the gas mass spectrometer signal shows CH 4 / CH in Ar atmosphere 4 The carbon deposition reaction occurs and generates H 2 , H 2 The amount first increased and then decreased, indicating that the amount of carbon deposits increased rapidly in the early stage and the growth rate gradually slowed down in the later stage; 2 CO / Ar atmosphere 2 The carbon removal reaction also occurs and generates CO. As the amount of carbon deposits decreases, the amount of CO generated also gradually decreases. The resistance signal of the catalyst is shown in CH 4 In the CO / Ar atmosphere, the resistance decreases continuously with the increase of carbon deposition amount, and 2 The resistance of the catalyst surface increased continuously with the decrease of carbon deposition under the Ar atmosphere, indicating that the carbon deposition on the catalyst surface can be monitored in real time through the change of resistance. Different from the result under the 3.3A current, the resistance of the catalyst surface under the Ar atmosphere after methane carbon deposition is significantly higher than that of the CO 2 The resistance in Ar atmosphere after carbon removal is small, which further shows that the carbon deposits on the catalyst surface can reduce the resistance of the foamed nickel-chromium-aluminum catalyst, and also means that current is flowing through the carbon deposits.

[0025] Comparative Example 1 This comparative example is a comparison of energy consumption between the method of the present invention and a conventional external heating method.

[0026] The catalyst, reactor, constant current power supply, etc. used are the same as those in Example 1. Conventional external heating is achieved by an electric heating furnace, and the power consumption of the electric heating furnace is measured by an electricity metering socket.

[0027] Carbon deposits are produced by methane cracking reaction under conventional external heating. The specific process is as follows: i. Ar (30 ml / min) was introduced into the reactor, and after the air was exhausted, the electric heating furnace began to heat up to 550°C; ii. CH is introduced into the reactor 4 6ml / min, Ar adjusted to 24ml / min; iii Observation by CH 4The H produced by the cleavage 2 After the mass spectrometer signal returns to the baseline, turn off the CH 4 At the same time, the Ar was adjusted to 30 ml / min, and the electric heating furnace was turned off and cooled to room temperature.

[0028] The process of removing the above carbon deposits by applying the present invention is as follows: i. Ar (30 ml / min) was introduced into the reactor. After the air was exhausted, the catalyst was energized to increase temperature, and the current was gradually increased to about 3A; ii. CO is introduced into the reactor 2 (6 ml / min) and reduce Ar to 24 ml / min; iii Waiting for CO 2 After the signal in the mass spectrometer stabilized, the current was increased at a rate of 0.035 A / min (temperature increase rate was about 4.3 °C / min) until the CO signal in the mass spectrometer returned to the baseline. The current was adjusted to zero and the CO was stopped. 2 .

[0029] The process of removing the above carbon deposits by conventional external heating is as follows: i. Ar (30 ml / min) was introduced into the reactor, and after the air was exhausted, the electric heating furnace began to heat up to 350°C; ii. CO is introduced into the reactor 2 (6 ml / min) and reduce Ar to 24 ml / min; iii Waiting for CO 2 After the signal in the mass spectrometer stabilized, the electric heating furnace was heated from 350°C at a rate of 4.3°C / min until the CO signal in the mass spectrometer returned to the baseline. 2 , the electric furnace is turned off and cooled to room temperature.

[0030] Figure 3 The CO of the above-mentioned method of the present invention and the conventional external heating method 2 Comparison of CO mass spectrometry signals during carbon removal, and comparison of the peak areas of the two 本发明 : A 外加热 =0.85:1, indicating that the two methods have little difference in carbon removal capacity. However, the power consumption of the two methods is 0.03 degrees and 0.38 degrees respectively (ratio is 0.08:1), which reflects the high energy efficiency advantage of the method of the present invention.

[0031] Example 2 This example illustrates the use of the method of the present invention to improve the catalytic activity of a methane dry reforming catalyst.

[0032] The catalyst used in this example is the nickel-chromium-aluminum foam structured catalyst prepared in Example 1. The hardware such as the reactor used and the method for calculating the electrically enhanced catalytic effect of the catalyst are as follows: Copper terminals are installed at both ends of a foamed nickel-chromium-aluminum structured catalyst as the first structured catalyst; another foamed nickel-chromium-aluminum structured catalyst is directly used as the second structured catalyst.

[0033] (1) Introduction to key equipment a) Catalytic performance evaluation reactor The catalytic performance evaluation of the first structured catalyst under "resistance internal heating" and the second structured catalyst under conventional external heating both use the same quartz tube reactor. The reactor consists of a 600 mm long, 11 mm inner diameter quartz main tube and a 200 mm long, 11 mm inner diameter quartz branch tube perpendicular to it. One end of the branch tube is connected to the middle position of the main tube. The main tube is used to place the catalyst and the flow of reaction gas, and the branch tube is used to insert a thermocouple to measure the temperature of the catalyst during conventional external heating.

[0034] b) Infrared thermal imager The temperature distribution of the first structured catalyst under "resistance internal heating" was measured using a Ti480PRO (FLUKE) infrared thermal imager. Its main technical indicators are: Infrared spectrum: 7.5 μm to 14 μm Detector resolution: 640×480 pixels Temperature measurement range: -20 °C to +800 °C Temperature measurement accuracy: ±2 °C or 2% c) Infrared thermal imaging reactor Since the infrared spectrum range required for the infrared thermal imager test cannot penetrate the quartz material used in the catalytic performance evaluation reactor, an infrared thermal imaging reactor with an infrared window (ZnSe window) is used to measure the temperature distribution of the first structured catalyst under set reaction conditions and set current (or electric power). The main body of the reactor is designed as a rectangular parallelepiped structure, in which the first structured catalyst is placed, and the ZnSe window serves as the upper surface reactor wall of the rectangular parallelepiped structure. The two ends of the first structured catalyst are connected to wires, and the two wires are respectively led out of the reactor through the gas inlet and the gas outlet and then connected to the positive and negative electrodes of the power supply. The catalyst is suspended and close to the lower surface reactor wall of the rectangular parallelepiped structure by the pulling force of the wire (direct contact between the two should be avoided to interfere with the temperature measurement), and the surface to be measured of the first structured catalyst is parallel to the ZnSe window and there is a distance of about 10 cm between the two, which can avoid the adverse effect of the high temperature generated by electric heating on the ZnSe material.

[0035] (2) Calculation method of electrically enhanced catalytic effect Step 1: Place the first structured catalyst along the axis of the quartz main tube in the middle of the catalytic performance evaluation reactor, connect copper wires at both ends of the catalyst, lead out from both ends of the reactor and connect to the positive and negative electrodes of a high-precision constant current DC power supply, and use current sensors and voltage sensors to monitor the current flowing through the catalyst and the voltage at both ends in real time, thereby calculating the electric power applied to the catalyst. The dry reforming reaction is carried out at normal pressure, and the reaction raw gas flows in from one end of the quartz main tube of the catalytic performance evaluation reactor and flows out from the other end. The composition of the outflowing gas is detected online by a gas chromatograph, thereby obtaining the apparent total catalytic activity results of the first structured catalyst under different currents (electric powers) of "internal resistance heating".

[0036] Step 2: Place the first structured catalyst in the main structure of the infrared thermal imaging reactor. Connect copper wires at both ends of the first structured catalyst and lead them out from the vents at both ends of the reactor and connect them to the positive and negative electrodes of a high-precision constant current DC power supply. Use the pulling force of the wires to suspend the catalyst in the air, and adjust the catalyst surface to be measured to be parallel to the ZnSe window. Install the infrared thermal imager on a tripod with the lens directly above the ZnSe window. Adjust the focal length of the lens to make the image of the first structured catalyst clear. Set the instrument parameters such as emissivity (0.7) and transmittance (99%). Introduce the reaction raw gas into the infrared thermal imaging reactor, and use the online gas mass spectrometer to monitor the changes in the outflow gas components in real time. Wait for CO 2 and CH 4 After the mass spectrometry signal is stable, infrared thermal imaging temperature measurement is started. First, when the first structured catalyst is not powered on, an ice bag is placed under the infrared thermal imaging reactor, and a thermal image is taken after the catalyst temperature is stabilized. The result is used to extract the outline of the first structured catalyst in the infrared thermal imaging image (i.e., the corresponding pixel point range). Then, the ice bag is removed, the relative position of the infrared thermal imager and the first structured catalyst is kept unchanged, and different current intensities are passed through the first structured catalyst from low to high. At each current, an infrared thermal image is taken after the catalyst temperature is stabilized.

[0037] Step 3: Place the catalytic performance evaluation reactor in an electric heating furnace for conventional external heating and temperature increase. The second structured catalyst is placed in the middle of the catalytic performance evaluation reactor along the axial direction of the quartz main pipe, and is also located in the middle of the heating zone of the electric heating furnace (200 mm long and 80 mm in diameter). A K-type thermocouple is inserted from the quartz branch pipe and placed close to the surface in the middle of the catalyst. The measurement result is used to represent the catalyst temperature. The dry reforming reaction is carried out under normal pressure. The reaction raw gas flows in from one end of the quartz main pipe of the catalytic performance evaluation reactor and flows out from the other end. The composition of the outflowing gas is detected online by a gas chromatograph, thereby obtaining the external heating catalytic activity results of the second structured catalyst at several discrete temperatures of conventional external heating. The curve of the external heating catalytic activity of the second structured catalyst changing with temperature is obtained by using a polynomial fitting method.

[0038] Step 4: Calculate the micro-region volume V of the first structured catalyst corresponding to a single pixel in the infrared thermal imaging image. 像素 (0.0098mm 3 ), and then according to V 像素 The volume ratio of the second structured catalyst (3.5 10 -5 : 1) and the results of the third step, a curve of the micro-region thermal catalytic activity of the first structured catalyst changing with temperature is obtained, and finally, based on the curve and the temperature distribution results obtained in the second step, the thermal catalytic activity of each micro-region on the first structured catalyst under different currents can be obtained.

[0039] Step 5: The overall thermal catalytic activity under the same current intensity (or electric power) is obtained by accumulating the thermal catalytic activities of all micro-regions on the first structured catalyst under the same current intensity (or electric power).

[0040] Step 6: Divide the overall thermal catalytic activity obtained in step 5 by the apparent total catalytic activity obtained in step 1 to obtain the thermal contribution, and then subtract the thermal contribution from 1 to obtain the electrical enhancement contribution.

[0041] Based on the above method, this embodiment respectively analyzes two reaction raw materials (the first is CO 2 : CH 4 =19.2 :10.8 ml / min, the second is CO 2 : CH 4 =15 : 15 ml / min) was used to calculate the electrical strengthening contribution of the foamed nickel-chromium-aluminum catalyst, and the main results are shown in Table 1.

[0042] Table 1

[0043]

[0044] From the results in Table 1, it can be seen that the CO in the raw gas 2 The increase in the ratio can significantly enhance the strengthening effect of electric energy on the catalytic performance of the foamed nickel-chromium-aluminum catalyst, that is, adding CO to the raw gas 2 The ratio is beneficial to accelerate the removal of carbon deposited on the catalyst surface, thereby improving the catalytic activity of methane dry reforming of the energized catalyst.

[0045] The present invention is not limited to the above-mentioned implementation modes, and any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for efficiently removing carbon deposits on a catalyst, characterized in that: The catalyst is electrified so that the carbon deposits on its surface pass through the current and react with CO2 to be removed.

2. The method according to claim 1, characterized in that: The temperature of the catalyst is adjusted by varying the current.

3. The method according to claim 1, characterized in that: The catalyst is a conductive structured catalyst.

4. The method according to claim 1, characterized in that: The active component of the catalyst contains Ni.

5. The method according to claim 1, characterized in that: The carbon deposits are formed by a methane cracking reaction.

6. The method according to claim 1, characterized in that: The change of the carbon deposit is monitored in real time through the change of the resistance of the catalyst.

Citation Information

Patent Citations

  • Method for regenerating light alkane dehydrogenation catalyst

    CN104084218A

  • Method for regenerating platinum-containing low carbon alkane dehydrogenation catalyst

    CN104107704A

  • Regeneration of spent paraffin dehydrogenation catalyst

    CN104507566A

  • Method for rapid removal of carbon deposits on surface of catalyst used for alkane dehydrogenation

    CN107971046A

  • HPPO method epoxypropane reactor and epoxypropane production method

    CN116983909A